Spatiotemporal Differences and Spatial Convergence of the Water-Energy-Food-Ecology Nexus in Northwest China - Wang, Min; Zhu, Yi-fei; Gong, Si-wen; Ni, Chang-yu (Frontiers in Energy Research, 2021)
Water-Energy-Food-Ecology Nexus is related to the realization of the goal of high quality economic development in Northwest China. This paper analyzed the dynamic change trend, spatial evolution characteristics and spatial convergence of identified W-E-F-E nexus in Northwest China utilizing the coupling coordination degree model, an ESDA instrument and spatial convergence model. The results show that: first, the W-E-F-E Nexus in Northwest China presents a "V" shaped trend of decreasing first and then rising in time dimension, which is after a 25.1 percent decline from 2002 to 2012, it rose 29.7 percent from 2012 to 2017. Second, W-E-F-E Nexus in Northwest China shows positive spatial autocorrelation. In spatial dimension, it shows a trend of high-value agglomeration around provincial capitals, and the distribution pattern is relatively stable. Thirdly, W-E-F-E Nexus in northwest China has significant spatial convergence, that is, the W-E-F-E Nexus gap between the prefectures in northwest China is shrinking, and the convergence rate is between 2.83 and 3.16. Moreover, with the development of economy, the rational allocation of land and labor resources, and the optimization of fiscal expenditure structure, the W-E-F-E Nexus of prefectures in Northwest China will converge to the same steady state level after a long period of time. In general, in the process of improving W-E-F-E Nexus in Northwest China, the heterogeneous characteristics of prefectures should be fully considered, and a trans-regional cooperative management and restriction mechanism of W-E-F-E Nexus should be explored to achieve high quality development of the region.